Field-induced self-assembly of iron oxide nanoparticles investigated using small-angle neutron scattering. Issue 43 (26th October 2016) - Fu, Zhendong; Xiao, Yinguo; Feoktystov, Artem; Pipich, Vitaliy; Appavou, Marie-Sousai; Su, Yixi; Feng, Erxi; Jin, Wentao; Brückel, Thomas
Abstract : The small-angle neutron scattering patterns show that iron oxide nanoparticles assemble into highly ordered three-dimensional aggregates in solution by applying external magnetic fields above 0.1 T. Abstract : The magnetic-field-induced assembly of magnetic nanoparticles (NPs) provides a unique and flexible strategy in the design and fabrication of functional nanostructures and devices. We have investigated the field-induced self-assembly of core–shell iron oxide NPs dispersed in toluene by means of small-angle neutron scattering (SANS). The form factor of the core–shell NPs was characterized and analyzed using SANS with polarized neutrons. Large-scale aggregates of iron oxide NPs formed above 0.02 T as indicated by very-small-angle neutron scattering measurements. A three-dimensional long-range ordered superlattice of iron oxide NPs was revealed under the application of a moderate magnetic field. The crystal structure of the superlattice has been identified to be face-centred cubic.